Does the Provision of Non-audit Services Affect Auditor Independence and Audit Quality? Evidence from Bahrain - Hussein Khasharmeh; Abdelmohsen M. Desoky (Asian Academy of Management Journal of Accounting and Finance, 2018)
The main aim of this research is to investigate perceptions of respondents (auditors, accountants and financial managers) on the effect of provision of non-audit services (NAS) to audit clients companies upon auditor independence and audit quality. This study expands on previous work done on the effects of providing non-audit services upon auditors’ independence and audit quality in Bahrain, which considered as an important subject for both auditing firms and auditing profession. This paper provides insights on the factors which explain the impact of the provision of non-audit services upon auditor independence and audit quality in Bahrain. To achieve the objectives of the research, a questionnaire was prepared and disseminated to a sample of 250 respondents. The results indicate that respondents are supporting the idea that “independence of auditor is impaired with providing non-audit service”. Kruskal-Wallis Test revealed that only respondents’ occupation is associated with their perceptions. Providing empirical evidence on this issue within the Bahraini environment, as a member of the Gulf Cooperation Council countries, may add a new dimension to the accounting and auditing literature. As the study analysed only one country (Bahrain); generalisation of the results might be a limitation. Future research studies should consider other countries in the region and to include respondents in other non-listed companies with more recent data which may lead to different results.